Screening Streptomycin Resistant Mutations from Gamma Ray Irradiated Bacillus subtilis B5 for Selection of Potential Mutants with high Production of Protease - Diep, Tran Bang; Thom, Nguyen Thi; Sang, Hoang Dang; Thao, Hoang Phuong; Binh, Nguyen Van; Thuan, Ta Bich; Lan, Vo Thi Huong; Quynh, Tran Minh (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: The suspensions of Bacillus subtilis B5, a rather high protease production strain, in logarithmic growth phase were irradiated under gamma Cobalt-60 source at Hanoi Irradiation Center. After treatment, the irradiated cells were intermediately cultured in the nutrient agar plates supplemented without and with 20µg/ml streptomycin for screening. The radiation effects on their viability and mutant frequency were studied with radiation dose. The results showed that its survival rate was reduced with the dose as biphasic function. The cells irradiated at dose higher than 1200 Gy do not form colony  in the medium containing streptomycin though they could  survive in nutrient agar. Therefore, potential streptomycin resistance mutations were collected as survivals from the cells irradiated with radiation dose ranging from 100 to 1000 Gy. Within this dose range, mutation frequency of Bacillus subtilis B5 increased with the rising dose. The greatest mutation frequency was determined as 1.61´10 -3 obtained by irradiation at 1000 Gy, and the smallest as 3.09´10 -6 at 100 Gy. The enzyme activities of 361 screened colonies from all irradiated samples were investigated in casein agar, and the results revealed 25 colonies having protease activity higher than parent strain. Keywords : Bacillus subtilis , gamma irradiation, streptomycin, survival, mutation frequency, protease.